(untitled) (Altre Modernità, 2018)
Irene Agudelo Builes, Contramemorias. Discursos e imágenes sobre/desde La Contra, Nicaragua 1979 1989 (Managua, IHNCA-UCA, 2017, 130 pp. ISBN 978-99924-29-18-1) por Silvia Gianni